Analytical solution of Klein Gordon equation Trigonometric Pӧschl-Teller potential using asymptotic iteration method - Dewanta Arya Nugraha; A Suparmi; C Cari (Journal of Physics: Theories and Applications, 2017)
Radial part of Klein Gordon equation for trigonometric Pӧschl-Teller potential was obtained within framework of a centrifugal term approximation. The relativistic energy spectrum and wave functions was obtain by using asymptotic iteration method. The value of relativistic energy was calculated numerically using Matlab 2013. The results showed that the relativistic energy is increasing due to the increase of potential constant and quantum number.